Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (Center for International Development, Harvard University, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Theory of Change in complex Research for Development programmes: challenges and solutions from the Global Challenges Research Fund - Chapman, Sarah; Boodhoo, Adiilah; Duffy, Carren; Goodman, Suki; Michalopoulou, Maria (The European Journal of Development Research, 2023)
The United Kingdom Research and Innovation (UKRI) Global Challenges Research Fund (GCRF) aimed to address global challenges to achieve the United Nations (UN) Sustainable Development Goals through 12 interdisciplinary research hubs. This research documents key lessons learned around working with Theory of Change (ToC) to guide Monitoring, Evaluation and Learning (MEL) within these complex research for development hubs. Interviews and document reviews were conducted in ten of the research hubs. The results revealed that only one hub invested in an explicit visual system mapping approach, and that funder timelines, budget constraints and issues with capacity and expertise limited the application of these approaches across all hubs. In contrast, many hubs attempted to deal with visual complexity by means of ether constructing multiple, nested ToCs, or a conscious simplification of complexity through reducing their ToC towards a straightforward and uncomplicated chain model or spherical model. While the former approach had some value, most hubs struggled to find capacity to support the full articulation of nested ToCs. In contrast, the latter approach resulted in ToCs which lacked detail or mechanism articulation, but which nevertheless were often ‘fit for purpose’ in ensuring effective communication and coherence across diverse stakeholders and sub-projects. We conclude that in instances where the reporting, funding and management cycles of complex research for development programmes cannot be adapted to properly support learning-based approaches to ToC development, imposing simplicity in the ToC might be fit for purpose. This might also be preferable to more complex visual approaches that are only partially realised.